Research, Development and Recent Patents on Aerodynamic Surface Circulation Control - A Critical Review - Djojodihardjo, Harijono; Thangarajah, Naveeyindren (Recent Patents on Mechanical Engineering, 2014)
The ever increasing demand for better performance of aircraft aerodynamics, from the fundamental understanding of flight, requires enhanced circulation. Circulation Control and hence its enhancement can be achieved by surface blowing in the form of Coanda jet and have always been referred to in the consideration of various flow control methods to enhance aerodynamic performance, along with continuous, synthetic and pulsed jets, compliant surface, vortex-cell, and the like. Coanda jet has also been applied in the development of novel aircrafts for short takeoff, while another circulation enhancement technique known as Trapped Vortex Cavity (TVC) is currently being given significant considerations. It is with such motivation that salient features, progress and development of various techniques in circulation control are here identified, including some of the recent inventions that have been registered as patents in this area. The present work reviews the influence, effectiveness and configuration of airfoil surface blowing of Circulation Enhancement and Control of aerodynamic surfaces. The crux of the TVC active research is their stabilization, while Coanda enhanced lift enhancement technique has, to a certain extent reached a stage that it can be easily implemented with advantage.
Keywords: trapped vortex cell